2020
DOI: 10.3390/polym12030679
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Magnetic Nanoparticles on Modified Polypyrrole/m-Phenylediamine for Adsorption of Cr(VI) from Aqueous Solution

Abstract: A novel, modified polypyrrole/m-phenylediamine (PPy-mPD) composite, decorated with magnetite (Fe 3 O 4 ) nanoparticles, and prepared via an in-situ oxidative polymerisation, was investigated. The PPy-mPD/Fe 3 O 4 nanocomposite was employed for the removal of highly toxic oxyanion hexavalent chromium Cr(VI) from an aqueous solution. The structure and successful formation of the PPy-mPD/Fe 3 O 4 nanocomposite was confirmed and investigated using various techniques. The presence of Fe 3 O 4 was confirmed by high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…It is urgent to develop various methodologies for elimination of Cr(VI) from water bodies. Various methodologies such as adsorption ( Ali and Gupta, 2006 ; Maponya et al, 2020 ), membrane filtration ( Kaya et al, 2016 ), solvent extraction ( Venkateswaran and Palanivelu, 2004 ), electrochemical precipitation ( Sun et al, 2015 ), coagulation ( Golbaz et al, 2014 ), bioremediation ( Beller et al, 2013 ; Benazir et al, 2010 ), ion exchange ( Xiao et al, 2016 ) and catalytic reduction ( Saikia et al, 2017 ) in addition to some traditional strategies ( Barrera-Díaz et al, 2012 ; Malaviya and Singh, 2011 ) based on reduction followed by precipitation have been employed for removal of Cr(VI) from aqueous medium. Although adsorption technology is an in-expensive and green methodology and does not involve formation of any side products.…”
Section: Introductionmentioning
confidence: 99%
“…It is urgent to develop various methodologies for elimination of Cr(VI) from water bodies. Various methodologies such as adsorption ( Ali and Gupta, 2006 ; Maponya et al, 2020 ), membrane filtration ( Kaya et al, 2016 ), solvent extraction ( Venkateswaran and Palanivelu, 2004 ), electrochemical precipitation ( Sun et al, 2015 ), coagulation ( Golbaz et al, 2014 ), bioremediation ( Beller et al, 2013 ; Benazir et al, 2010 ), ion exchange ( Xiao et al, 2016 ) and catalytic reduction ( Saikia et al, 2017 ) in addition to some traditional strategies ( Barrera-Díaz et al, 2012 ; Malaviya and Singh, 2011 ) based on reduction followed by precipitation have been employed for removal of Cr(VI) from aqueous medium. Although adsorption technology is an in-expensive and green methodology and does not involve formation of any side products.…”
Section: Introductionmentioning
confidence: 99%
“…The negative ∆ G values indicated that the adsorption was spontaneous. The positive ∆ S indicated there was a high affinity between rare earth ions and the resin [ 41 ]. The adsorption was an endothermic chemical adsorption.…”
Section: Resultsmentioning
confidence: 99%
“…PPy-mPD/Fe 3 O 4 nanocomposite is a potential adsorbent for Cr(VI) removal due to its high adsorption capacity and selectivity. It is also a very low-cost super-adsorption material for heavy metal ions [ 167 ].…”
Section: Nanotechnology-based Heavy Metal Removal In Food and Watermentioning
confidence: 99%